Morphological and multi-gene phylogenetic analyses of two new species of Phyllosticta (Phyllostictaceae, Botryosphaeriales) from Southwestern China - Gong, Cui-Ling; Wu, Hai-Xia; Li, Jin-Chen; Song, Jia-Yu (Phytotaxa, 2024)
Phyllosticta is an important genus of pathogenic fungi with worldwide distribution. Phyllosticta species also occur as endophytes and saprobes on various plant hosts. Multi-gene phylogenetic analysis based on sequence data of ITS, LSU, TEF1 and morphological evidence supported the introduction of two new species, which were isolated from dead leaves in China. Phylogenetically, the new species, P. savannaensis and P. ovalina, formed two well-separated lineages in the Phyllosticta capitalensis and Phyllosticta cruenta species complexes, respectively. P. savannaensis is closely related to P. capitalensis, but formed a separate branch (BS= 100%/BYPP= 1.0), while P. ovalina and P. hubeiensis clustered together with high support (BS= 100%/BYPP= 1.0). Both new species exhibited the typical characteristics of the genus Phyllosticta but could be distinguished from closely related species. P. savannaensis can be differentiated from the sexual stage of other Phyllosticta species by the length to width ratio of the ascospores and shape of appendages. The ascospores of P. ovalina are oval, which distinguish it from other species of Phyllosticta.